Memorization and the Compound-Phrase Distinction : an Investigation of Complex Constructions in German, French and English. - Schlechtweg, Marcel (Studia grammatica., 2018)
Over the last decades, it has been hotly debated whether and how compounds, i.e. word-formations, and phrases differ from each other. The book discusses this issue by investigating compounds and phrases from a structural, semantic-functional and, crucially, cognitive perspective. The analysis focuses on compounds and phrases that are composed of either an adjective and a noun or two nouns in German, French and English. Having distinguished compounds from phrases on structural and semantic-functional grounds, the author claims that compounds are by their nature more appropriate to be stored in the mental lexicon than phrases and supports his argument with empirical evidence from new psycholinguistic studies. In sum, the book maintains the separation between compounds and phrases and reflects upon its cognitive consequences.